Identification of HEV in symptom‐free migrants and environmental samples in Italy. Issue 6 (26th December 2012) - Idolo, A.; Serio, F.; Lugoli, F.; Grassi, T.; Bagordo, F.; Guido, M.; Privitera, G.; Lobreglio, G.; De Donno, A.
Summary Hepatitis E virus (HEV) is considered an emerging pathogen in industrialized countries. The occurrence of HEV genotypes in samples of faeces from asymptomatic migrants arriving on the coasts of South Italy and environmental samples was investigated. Analyses of sequences were used to compare human and environmental genotypes. A total of 40 stool specimens, 12 samples of untreated urban sewage, 12 samples of treated urban sewage and 12 samples of surface water were analysed. Viruses were concentrated from water samples by the tangential flow ultrafiltration technique. The presence of HEV RNA was detected by nested RT‐PCR. Viral isolates were sequenced and phylogenetically characterized. Two (5%) of the 40 faecal samples tested were found to be positive for HEV RNA (G1 and G3 genotypes). The virus was detected in 25% (3/12) of the untreated sewage samples and 25% (3/12) of the surface water samples: all isolates belonged to G3 genotype. None of the treated sewage samples were found to be HEV RNA positive. The virus was detected in the faeces of two asymptomatic subjects, suggesting a potential role for symptom‐free HEV carriers as a human reservoir. G3 HEV strains were detected in the untreated sewage, as observed in similar studies conducted in other European countries but differing from another study conducted in Italy recently. Moreover, our results show the first case of HEV isolated from fresh surface waters.